The Influence of Debit Card, Credit Card, and E-Money Transactions Toward Currency Demand in Indonesia - Saraswati, Nurma; Mukhlis, Imam (Universitas Negeri Malang, 2018)
This study aims to determine the effect of debit card transactions, credit card transactions and e-money transactions to currency demand in Indonesia. This research using model estimation Vector Error Correction models (VECM). The data was collected using secondary data obtained from the website of Bank Indonesia and Bureau Central of Statistic in Indonesia. The data were obtained from January 2009 to August 2017 consisting of debit card transaction, credit card transaction, e-money transaction, and cash amount data in circulation data. The findings showed that debit card transactions have a significant negative effect on the demand for currency in Indonesia in the long term, credit card transactions have a significant positive effect on the demand for currency in Indonesia in the long term, while e-money transactions have a significant positive effect on currency demand in Indonesia in the short and long term.Keywords: E-money; Currency demand; Debit card; Credit cardJEL Codes: E41; E51